Analisis Pemeriksaan Kesehatan Koperasi Syariah Berdasarkan Petunjuk Teknis Deputi Perkoperasian Nomor 15 Tahun 2021 - Dewi Rahmawati; Angga Septian Prayoga (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
The full application of cooperative identity and measurement of cooperative financial performance is necessary for the development of cooperatives and increasing public trust in cooperatives. The purpose of this study was to analyze the health of sharia cooperatives in Jepara Regency based on the Technical Instructions of the Deputy for Cooperatives Number 15 of 2021. The data used is secondary data obtained from the Financial Reports of Islamic Cooperatives closing the books for 2021 – 2022. The research method used is descriptive quantitative through the Cooperative Health Examination Working Paper (KKPKK) in accordance with the Technical Instructions of the Deputy for Cooperatives Number 15 of 2021. The research population is sharia cooperatives in Jepara Regency. The sample refers to 5 sharia cooperatives. The results of the analysis show that the overall health level of 5 sharia cooperatives in Jepara Regency in 2021-2022 is in the fairly healthy category with a score of 66-79 and 1 cooperative with a Healthy predicate with a score of 80.22. The implementation of this research is so that it can become a guide for cooperatives in implementing cooperative identity, compiling a complete Cooperative Internal Control Standard, so that it can become a cooperative improvement and development and increase member and community trust in the cooperative